(untitled) (Journal of Hama University, 2022)
The study was conducted on rabbits males at ages 6 months. The target of the study was to knowledge the impact each of alcohol extraction of fenugreekseeds and nigella stiva.seeds in the healthy rabbits weight rates and to conclude the effect of the mentioned extraction a liver enzymes activity (ALT, AST) in disordered functional in liver activity using 4th Carbon Chloride.The population study were divided into 10 groups, the first group was coded as G1 (included 6 rabbits), and considered as control group, It had been provided with water and food only, the second group was included 6 rabbits and coded as G2 that was taken alcohol extraction of fenugreekwith dose 500 mg /kg while G3 group was included 6 rabbits and taken alcohol extraction of fenugreek with dose 1000 mg/kg. The fourth group was coded as G4 and involved 6 rabbits that were taken alcohol extraction of Nigella Stivawith dose 200 mg./kg. The fifth group was coded as G5 and involved 6 rabbits that were taken alcohol extraction of Nigella Stivawith dose 300 mg./kg. The sixth group was coded as G6 and involved 6 rabbits that were taken dose as 1 ml/kg of live weight of 4th Carbon Chloride weekly for 4 weeks. The seventh group was coded as G7 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of fenugreekwith dose 500 mg /kg. The eighth group was coded as G8 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of fenugreekwith dose 1000 mg /kg. The ninth group was coded as G9 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of Nigella Stivawith dose 200 mg./kg. The tenth group was coded as G10 and involved 6 rabbits that were effected with disordered functional liver using 4th Carbon Chloride and taken alcohol extraction of Nigella Stivawith dose 300 mg./kg. Results showed that dealing of rabbits with both extractions given significant increase in healthy rabbits weights (p<=0.05). As long as dealing with effected rabbits in functional disordered liver in both extractions leaded to significant decrease in liver enzymes activity (ALT, AST) in effected rabbits via functional disordered liver compare to fourth group which none taken an extractions.